Some considerations about the M|G|∞ queue approximation by a Markov renewal process - Ferreira, Manuel Alberto M. (2013)
Some M|G|∞ queue systems interesting quantities values approximations, obtained through the consideration of an adequate Markov renewal process, are presented and studied.